PERBANDINGAN LATIHAN MENGGUNAKAN MEDIA BOLA TENIS DAN MODIFIKASI TURBO TERHADAP HASIL LEMPAR LEMBING - Dika, Yuliana; Purnomo, Edi; Samodra, Tauvan Juni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractProblems in this research is how influence of media giving of tennis ball ball and turbo modification to javelin result in student of class XI SMK Negeri 1 Pontianak. The purpose of this research is to know the comparison of tennis ball media and turbo modification to javelin yield. The research design used Two group pretest-posttes design. The population in this study is the students of class XI which amounted to 60 people. Sampling technique in this research using random sampling technique. In this study, researchers will take 28 students consisting of 14 samples for treatment with tennis ball media and 14 samples for turbo modification treatment. Tenik data collection with tests and measurements. Data analysis technique using t-test. Result of research and data analysis hence there is influence of exercise using ball of tennis media against to result of student javelin throw. There is an effect of the exercise using turbo modification on the results of the student's javelin throw. Exercises using turbo modification media have a better influence than the tennis ball media on the ability of students' javelin results with 1.30 or 6.81%.Â Keywords: Tennis Ball Media, Turbo Modification, Javelin Throw.